The British Parliament's Position on the American and French Revolutions (Journal of the College of Basic Education, 2025)
Parliament is, in fact, the state body most directly implementing international treaties and other domestic legislation. It is also managing meetings in an organized manner. When people hold a meeting, they need systems to help them achieve their goals and objectives. The root of the British Parliament go back to the period between the eighth and eleventh centuries AD. Parliament is a term derived, the French word "parler," which means council. It also refers to discussion, debate, or discussion. The era of King George III marked an important. stage in modern British history due to its significant role and influence in the development of parliamentary life in Britain. Parliament played a prominent role in the issues of the American and French revolutions, British positions in regard to the French Revolution varied between indifference, neutrality, support, and opposition. The divsion of British, Public opinon at home, the opposition to the war with the colonies, and the oposition of members of the House of Comons, to the war project, Greatly weakened, the king's position in preparing the necessary military forces, forcing him To Rely on German merenaries and other in the war with the American colonies, which greatly harmd the kings position. the reputaion of Britain and its governmnt in the colnies.